Disease and economic burden increase with systemic lupus erythematosus severity 1 year before and after diagnosis: a real-world cohort study, United States, 2004–2015 - Barnabas Desta; Edward R Hammond; Miao Jiang; Aimee M Near (Lupus Science and Medicine)
Objective To assess the economic burden of patients with SLE by disease severity in the USA 1 year before and after diagnosis.Methods Patients aged ≥18 years with a first SLE diagnosis (index date) between January 2005 and December 2014 were identified from administrative commercial claims data linked to electronic medical records (EMRs). Disease severity during the year after diagnosis was classified as mild, moderate, or severe using claims-based algorithms and EMR data. Healthcare resource utilisation (HCRU) and all-cause healthcare costs (2017 US$) were reported for 1 year pre-diagnosis and post-diagnosis. Generalised linear modelling examined all-cause costs over 1 year post-index, adjusting for baseline demographics, clinical characteristics, Charlson Comorbidity Index and 1 year pre-diagnosis costs.Results Among 2227 patients, 26.3% had mild, 51.0% moderate and 22.7% severe SLE. Mean per-patient costs were higher for patients with moderate and severe SLE compared with mild SLE during the year before diagnosis: mild US$12 373, moderate $22 559 and severe US$39 261 (p<0.0001); and 1-year post-diagnosis period: mild US$13 415, moderate US$29 512 and severe US$68 260 (p<0.0001). Leading mean cost drivers were outpatient visits (US$13 566) and hospitalisations (US$10 252). Post-diagnosis inpatient utilisation (≥1 stay) was higher for patients with severe (51.2%) and moderate (22.4%) SLE, compared with mild SLE (12.8%), with longer mean hospital stays: mild 0.47 days, moderate 1.31 days and severe 5.52 days (p<0.0001).Conclusion HCRU and costs increase with disease severity in the year before and after diagnosis; leading cost drivers post-diagnosis were outpatient visits and hospitalisations. Earlier diagnosis and treatment may improve health outcomes and reduce HCRU and costs.